Effects of Aframomum danielli(powder and extracts) on the nutritional, physico-chemical and sensory properties of wheat flour bread (2008)
The effects of adding different concentrations of Aframomum danielli (powder and ethanoic extracts) on nutritional, physico-chemical and sensory properties of wheat flour bread were examined. A. danielli powder – 2, 4 and 6%, and ethanolic extract (0.1 and 0.2%) were added, respectively, to flour. Using alveograph and consistograph, the physical properties of the dough-water absorption capacity, tenacity, extensibility, strength of flour and peak time were evaluated. As the concentration of A. danielli in the dough increased from 0 to 4%, alveograph tenacity increased from 96 to 193 mm H2O, extensibility decreased from 92 to 27 mm, gluten decreased from 12.21 to 10.56 mm, flour strength decreased from 365 to 255 while consistograph water absorption capacity increased from 56.8 to 58.9%. A 24-member panel familiar with spiced bread found that bread with A. daniell flavour and having no quality impairment can be made with 2% A. danielli powder and 0.1-0.2% ethanolic extract. The lower the level of A. danielli powder addition, the more acceptable the loaf to the taste panellists as the golden brown colour of the crust, texture and uniform crumb grain of spiced bread were similar to those of the control bread sample.